Understory contrasts across experimental tropical forest restoration - Luis C. Beltrán; Marinés de la Peña-Domene; Henry F. Howe; Camila A. Marín-Marín; Flavio Márquez-Torres; Edith Rivas-Alonso; Lilia L. Roa-Fuentes; Neptali Sánchez; Cristina Martínez-Garza (Forest Ecology and Management, 2026)

Technological variability and raw material procurement in the Cantabrian Lower Magdalenian: Level G1 at El Cierro Cave (Ribadesella, Asturias, Spain) - Diego Herrero-Alonso; Sergio Martín-Jarque; Antonio Tarriño; David Álvarez-Alonso; Selina Delgado-Raack; Alejandro Prieto; Jesús F. Jordá Pardo; Esteban Álvarez-Fernández (Archaeological and Anthropological Sciences, 2026)
This paper presents a comprehensive analysis of the lithic assemblage from Level G1 of El Cierro Cave (northern Spain), attributed to the Cantabrian Lower Magdalenian. The study comprises 2,829 items, including 2,800 knapped artefacts, six macrolithic tools and 23 unmodified pebbles. Lithic procurement is dominated by flint, followed by quartzite and minor amounts of quartz. Eleven flint types have been identified, with local raw materials prevailing, while regional and tracer groups occur in lower proportions, indicating selective long-distance connections within the Basque-Cantabrian Basin. Technological analysis reveals complete operational chains for flake production using locally available resources, alongside greater variability in laminar reduction strategies. Blade production is limited and clearly subordinate to flake-oriented technologies. The retouched tool assemblage, dominated by endscrapers, conforms to typical Upper Palaeolithic techno-typological patterns, whereas backed bladelets are poorly represented. Use-wear analysis indicates a range of activities involving macrolithic tools, potentially linked to both lithic production and the processing of organic materials. Overall, the Level G1 assemblage at El Cierro is characterised by a strong reliance on local raw materials, restricted circulation of distant flints and low investment in laminar production, reflecting procurement strategies operating primarily at a local scale and a technological organisation adapted to domestic activities and reduced mobility.

Controlled co-delivery of anti-inflammatory drugs from bilayer polymer films coating a meniscus implant - Alfonso F. Blanco; Gustavo Lou; Alba Pensado-López; Aldo Ummarino; Fernando Torres Andón; José Crecente-Campo; María José Alonso (Drug Delivery and Translational Research, 2026)
Knee osteoarthritis (OA), a degenerative joint disease, is increasingly prevalent worldwide and often results from a meniscal deterioration that leads to meniscus removal. Replacing the damaged meniscus with a non-biodegradable prosthesis offers an innovative solution to prevent OA progression, particularly in older patients. However, the long-term use of anti-inflammatory drugs for pain relief and prosthesis integration can cause severe off-target side effects. The objective of this work was to design and develop drug-loaded bilayer polymer films to be used as coatings for a meniscus polycarbonate urethane (PCU). The developed bilayer polymer films enabled a sustained release of two anti-inflammatory drugs - dexamethasone (DEX) and celecoxib (CLX) - with distinct release kinetics (1–4 weeks for DEX and 6–9 months for CLX). This release profile was defined to modulate post-surgical and chronic inflammation within the knee joint, respectively. Two bilayer prototypes showed consistent biodegradation, drug release, drug loading, and reproducibility. Furthermore, the systems were sterile, biocompatible, and maintained the anti-inflammatory efficacy of the released drugs, effectively reducing pro-inflammatory cytokine secretion from human primary macrophages.

Dietary mixed microalgae modulate growth and fatty acids of the copepod Apocyclops spartinus - Wilmer Gaspar-Reyes; Leenin Flores Ramos; Gheraldine A. Ynga-H.; Alexander F. Niño-V.; Ruth M. Alejos-Cabrera; Pedro Pablo Alonso Sánchez-Dávila; Cecil Tenorio; Víctor Aramayo (Aquaculture, 2026)

Development of a cationic bionanocomplex from N-aryl-chitosan derivatives for controlled drug release - Samir E. Esquivel; Matías Rebolledo; Elizabeth R. Gilles; Carolina Gomez-Gaete; Víctor H. Campos -Requena; Jorge R. Toledo Alonso; Manuel F. Meléndrez; Daniel A. Palacio (Carbohydrate Polymers, 2026)

Bioacoustic Baselines for Intact Forests - Z. Buřivalová; S. Perea; L. M. Berman; H. S. S. C. Sagar; T. M. Maeda; N. Yoh; G. Ingram; M. Persche; C. Mere‐Roncal; A. Lopera‐Toro; E. Chaboteaux; R. Rumelt; et al. (Global Change Biology, 2026)
Forests are at the frontline of both climate and biodiversity crises: forests are fundamental to the regulation of Earth's atmospheric carbon dioxide levels, and tropical forests alone harbour over half of all terrestrial species. Consequently, forests are at the centre of global efforts to both prevent extinctions of species and sequester carbon to mitigate climate change. Most carbon sequestration initiatives do not measure how effective they are in terms of biodiversity protection, largely because it is expensive, complex and often not required. Compounding this problem is the lack of reliable biodiversity baselines, against which positive changes due to conservation and negative changes due to human pressure could be measured. The Soundscape Baselines Project is a global initiative to collect and analyse bioacoustic baselines in some of the world's remaining intact forests. The baseline data are collected using a modular system of passive acoustic monitoring and ancillary data that can be expanded and integrated with other technologies. It is managed by local teams of scientists, conservation practitioners and community members. Emphasis is on the usability of data and equipment beyond the project, community engagement and building an interconnected network of scientists across forested countries, particularly historically underexplored partnerships between tropical forest countries. In this paper, we describe the initiative and share initial results to demonstrate how the project could be used for biodiversity conservation purposes in the future and outline steps towards operationalization. We also draw a list of priority areas for additional baseline locations across remaining intact forests. We discuss how bioacoustic baselines established now and in the future will become invaluable in a rapidly changing climate and the resulting unprecedented change in Earth's forests. Establishing rigorous biodiversity baselines using bioacoustics and other technologies and approaches through collaborative science is fundamental to ground biodiversity conservation in evidence, equity and transparency.

Epigenomic response to insect herbivory in Lombardy poplar: assessing geographic variation in DNA methylation changes - Mónica Medrano; A. Niloya Troyee; Cristian Peña-Ponton; Koen J. F. Verhoeven; Conchita Alonso (Tree Genetics & Genomes, 2026)
DNA methylation is a key epigenetic mechanism in plants, reported to be involved in regulating responses and local adaptation to abiotic and biotic stressors that could be particularly beneficial for long-lived tree species. Given that climate change is predicted to promote insect outbreaks, epigenetic studies of herbivory responses in trees may be vital for forest management and conservation. Here, we study changes in DNA methylation in response to herbivory in the clonal tree Populus nigra cv. ‘italica’ (Lombardy poplar). Cuttings were collected from three distant geographical locations (Spain, Italy, Poland), clonally replicated and grown in a common environment. We used reduced representation bisulfite sequencing to assess methylation changes between three experimental categories: (i) insect and (ii) artificial herbivory, and (iii) undamaged plants. Our results indicate that DNA methylation in poplars from different provenance, despite being genetically very similar, responded differently to experimental herbivory with plant origin accounting for 17.2% of the variation across CG, CHG, and CHH contexts. Both insect and artificial herbivory induced a significantly higher response in CHH context. When we explore loci with contrasting methylation levels (differentially methylated cytosines, DMCs), Spanish poplars were the most responsive to insect damage while Polish trees to artificial herbivory. DMCs were primarily located in gene bodies and their flanking regions (CG, CHG) or intergenic regions (CHH). Further, about one-third of DMCs obtained in CHH context were associated with transposable elements (TEs). Our findings suggest that for a better understanding of the role of the epigenetics in plant responses to herbivory we may need to take into account history of exposure, and highlight the importance of incorporating epigenetic knowledge to manage natural forests and tree plantations to help them cope with their environmental challenges.

Consistent Microbial Assembly in the Rhizosphere of Crop Wild Progenitors - Miguel de Celis; María José Fernández‐Alonso; María Leo; Ignacio Belda; Carlos García; Brajesh K. Singh; Yue Yin; Juntao Wang; Juan Gaitán; Luis Abdala‐Roberts; Fernando D. Alfaro; Diego F. Angulo; et al. (Global Ecology and Biogeography, 2026)
Aim Microbiome rewilding seeks to harness plant‐microbe interactions for sustainable agriculture, assuming that ancestral microbial partners have been lost during domestication and geographical spread. Designing microbiome rewilding strategies requires a quantitative and predictive understanding of the fundamental ecological processes—selection, dispersal, and drift—driving microbial assembly and persistence in the rhizosphere of crop wild progenitors (CWPs). Location Global. Time Period Present. Major Taxa Studied Rhizosphere bacteria and fungi. Methods Here, we leveraged a global survey of the CWPs of 10 major crops across their native habitats to assess the roles of selection, dispersal, and drift in shaping rhizosphere microbial communities. We combined compositional and phylogenetic turnover metrics with local network analyses to evaluate community assembly and structure in response to environmental gradients. Results We found host‐driven selection, reflected by low phylogenetic turnover at the whole‐tree level, but also selection driven by differences among individual plants, as indicated by high turnover among closely related taxa. The high level of compositional turnover found suggests dispersal limitations, which in the context of CWPs, may indicate host‐mediated filtering of external microbial taxa. The network structure was constant across CWPs; however, bacterial and fungal structures diverged, pointing to distinct community organisations. Bacterial communities presented higher modularity and lower clustering than fungal communities. Climate, especially seasonal temperature and precipitation, was the main driver of both bacterial and fungal structures. However, host identity best predicted bacterial structure, while NDVI, a proxy for vegetation status, better explained fungal patterns. Main Conclusions Bacterial and fungal communities are shaped by consistent assembly processes across CWPs, but their structures diverge. With the identification of the assembly processes driving microbiome composition in the rhizosphere of CWPs, this work paves the road to incorporate microbiome rewilding in the toolbox of sustainable agriculture.

Genetic testing for hereditary breast and ovarian cancer in the Murcian population using a comprehensive NGS panel - Y. Mestre Terkemani; L. Rosado Jiménez; A. García Aliaga; M. D. Sarabia Meseguer; M. Marín Vera; J. A. Macías Cerrolaza; P. Sánchez Henarejos; M. R. García Hernández; M. Zafra Poves; B. Alvarez Abril; E. García Torralba; C. B. López Sánchez; et al. (Familial Cancer, 2026)

Pathological and epidemiological assessment of cranial crassicaudiasis in stranded cetaceans from the Canary Islands (1999–2024) - Zuleima Suárez-González; Antonio Fernández; Jorge F. González; Noelia Salgado-Jiménez; Ignacio Molpeceres-Diego; Paula Alonso-Almorox; Eva Sierra (Research in Veterinary Science, 2026)

Multivariate assessment of groundwater contamination levels associated with saline intrusion processes in Mediterranean coastal aquifers - R. Álvarez-Alonso; P.A. Robledo Ardila; S. Deudero; C.A. Melo-Aguilar; C. Alomar; F. Micheo; J.J. Durán; S. Pérez; F. Árcega Cabrera; S. Martínez Pérez (Journal of Contaminant Hydrology, 2026)

Strategic use of enzyme-linked immunosorbent assay as a complementary tool for the diagnosis of bovine tuberculosis - C. Camussone; R.D. Moyano; M.N. Alonso; J. Cicotello; A. Peña; A.I. Molineri; D.M. Astesana; G. Suárez-Archilla; F. Tello D'Elia; D. Aliprandi; N.M. Welschen; M.L. Signorini; et al. (Research in Veterinary Science, 2026)

Effects of DNA-demethylation on the expression of plastic and transgenerational responses to nitrogen availability in annual plant species - Vanessa Minden; Conchita Alonso; Harry Olde Venterink; Koen J. F. Verhoeven (Evolutionary Ecology, 2026)

Impact of psychiatric disorders on treatment adherence and overall survival in patients with Hodgkin lymphoma: a retrospective cohort study - Gerardo Santiago-Jiménez; Alonso Hernández-Company; Josheline G. Ramírez-Jaramillo; Lena G. Simental-Legarda; Efreen H. Montaño-Figueroa; Christian O. Ramos-Peñafiel; Humberto B. Castellanos-Sinco; Emmanuel Martínez-Moreno; Juan F. Zazueta-Pozos; Gilberto I. Barranco-Lampón; Carlos Martínez-Murillo (Cancer Causes & Control, 2026)

Publisher Correction: Livestock husbandry in Islamic Cártama, Málaga, Spain: The micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2026)

Experimental, simulation and process design of hydrogen production from biomass-based products co-gasification in supercritical water - Rafael F. Rezende; Guilherme B.M. de Souza; Lucas C. Mourão; Isabela M. Dias; Annamaria D.S. Vidotti; Antonio C.D. de Freitas; Leandro V. Pavão; Belen García-Jarana; Jose M. Abelleira-Pereira; Juan R. Portela; Lucio Cardozo-Filho; Reginaldo Guirardello; et al. (Fuel, 2026)

Detection of Microplastics in Commercial Mussels: Unveiling Hidden Environmental Pollutants - G. García-Rosales; C.M. Alonso-Hernández; F. Oberhaensli; L.C. Longoria-Gándara (Regional Studies in Marine Science, 2025)

Multi-component tree biomass approach to estimate litterfall Hg deposition in a warm-temperate coniferous forest in southern Europe - A. Parente-Sendín; M. Méndez-López; N. Calvo-Portela; L. Acemel-Míguez; F. Alonso-Vega; J.C. Nóvoa-Muñoz (Environmental Research, 2025)

Livestock husbandry in Islamic Cártama, Málaga, Spain: the micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2025)
Multidisciplinary micro- and bioarchaeological analyses of late medieval deposits from suburban Cártama, Málaga, Spain, have, for the first time, confidently identified open air fumier deposits, which are supported by preliminary analysis of the faunal assemblage. This demonstrates that Andalusi livestock husbandry practices included periodically burning animal dung within corrals and pens, which is a long-standing practice in the Mediterranean region also observed in prehistoric transhumance. These techniques have commonly been applied to prehistoric fumier or pastoral sites and now demonstrate the importance of expanding micro- and bioarchaeological work to fumier sequences from other periods. This research from Cártama offers a window into the so-called medieval “Green Revolution” associated with Arab migrations and highlights the necessity of identifying in situ penning deposits on archaeological sites and of applying high resolution analyses to examine them. The analyses reveal data on animal feeds, including pearl millet ( Pennisetum glaucum ) and sorghum ( Sorghum bicolor ) which are rare in the Iberian Peninsula at this time, the use of plant resources in livestock husbandry, and the preparation of fertiliser, which are central to understanding farming practices in Al-Andalus.

Elucidating the neuromeric organization of the Mongolian gerbil brain - F. Lucero-Arteaga; S. Labegorra; A. Abrego-Alvarez; V. Heck; A. I. Portu; M. A. Boeris; A. Alonso; B. Ribeiro Do-Couto; M. Á. García-Cabezas; K. Y. Tseng; José Luis Ferran (Brain Structure and Function, 2025)
The Mongolian Gerbil ( Meriones unguiculatus ) diverged from rats/mice around 45 million years ago and developed adaptations to extreme temperatures and water scarcity. Another feature of the Mongolian Gerbils is their social monogamy similar to that of prairie voles. These observations suggest that there are potential differences in the Mongolian Gerbil brain that are distinct from that of rats and mice. The goal of the present study is to establish the extent to which the neuromeric organization of the brain is conserved in the Mongolian Gerbil and to gain insights on how evolutionary expansion and diversification of brain regions occur across species. Our data shows that the multineuromeric origin of tyrosine hydroxylase-positive processes in the Mongolian Gerbil is similar to that in mice and rats, spanning from the diencephalon, midbrain, and the rostral hindbrain. There are also observable anatomical differences. However, most of the components characteristic of these neuromeres are identifiable in the Mongolian gerbil, closely mirroring those found in mice and rats. Together, these findings suggest that the conserved neuromeric organization likely stems from a restricted genetic toolset that began in the Muridae family 45 million years ago, and that a profound reorganization of the fundamental structural plan delineating the neuromeric segmentation is not required for the emergence of diverse functionality among species of phylogenetically related families. Future studies are needed to establish how the genetic programs within each neuromeric unit are influenced by environmental factors that ultimately impact the size of the neuromeric derivatives and their functional connectivity.

Thermo-hydro-mechanical responses of a high-level radioactive waste repository: Effects of short- and long-term nonlinear behavior of the host rock - M.N. Vu; C. Plúa; G. Armand; F. Bumbieler; C. De Lesquen; M. Souley; M. Alonso; J. Vaunat; A. Gens; Z. Yu; J.F. Shao (International Journal of Rock Mechanics and Mining Sciences, 2025)

Three-dimensional discrete magnetic inversion using graph theory to determine the framework of isolated sources - Rômulo Rodrigues de Oliveira; Rodrigo Bijani; Nelson Ribeiro-Filho; Edson Alonso Falla-Luza; Cosme F. Ponte-Neto (Journal of Applied Geophysics, 2025)

Gamma radiation in highly compacted FEBEX bentonite: Key microbial and mineralogical behavior for safety assessment of nuclear repositories - Mar Morales-Hidalgo; Cristina Povedano-Priego; Marcos F. Martinez-Moreno; Kateřina Černá; Klára Lísková; Jakub Říha; Pedro Valdivieso; Ursula Alonso; Ana María Fernández; Fadwa Jroundi; Mohamed L. Merroun (Journal of Hazardous Materials, 2025)

Impact of composts from decentralized composting models on R. officinalis physiology and nutrient contents under abiotic stress - C. Álvarez-Alonso; I. Nogues; E. Pallozzi; W. Stefanoni; F. Pietrini; L. Sosa; N. Manrique-Cordoba; M.D. Perez-Murcia; R. Moral; M.A. Bustamante (Journal of Environmental Management, 2025)

A Comprehensive Database of Expert‐Curated Occurrences for the Genus Carex L. (Cyperaceae) - María Sanz‐Arnal; Pablo García‐Moro; Carmen Benítez‐Benítez; Marina Coca‐de‐la‐Iglesia; Angélica Gallego‐Narbón; Consolación Barciela; Fabrizio Bartolucci; Prabin Bhandari; Matthew Bradley; Asunción Cano; Antoine Derouaux; Sabina Donadío; et al. (Global Ecology and Biogeography, 2025)
Motivation Geographic occurrences are essential for biodiversity studies, but publicly available repositories like GBIF often contain errors and biases, especially for taxonomically complex groups like Carex L. (Cyperaceae). This work provides an expert‐curated global dataset of occurrences compiled from different sources to enhance data accuracy and usability. The final dataset includes 384,067 occurrences of 1790 Carex species. Main Types of Variables Contained The dataset includes species occurrence records with geographic coordinates, taxonomic identifications, and curation flags (e.g., introduced, erroneous records). Spatial Location and Grain The dataset covers a global scale, using the WGS84 projection. Spatial resolution is standardised to a minimum of three decimal degrees (~1 km, if possible). Time Period and Grain Online records span from 1950 to 2020, but some manually georeferenced records are earlier (1850). There is also fieldwork data after 2020, specifically up to 2023. Major Taxa and Level of Measurement Cyperaceae: Carex . Most records have species‐level identification, and some of them are identified at subspecies or variety levels. Software Format Data are supplied as comma‐separated values files with UTF‐8 encoding.

Heterogeneous provenance and intracontinental rift evidence in the early–middle Jurassic La Boca Formation in the Huizachal-Peregrina Anticlinorium, Mexico - Jorge Enrique Ruiz-Urueña; Michelangelo Martini; Mildred Zepeda-Martínez; Juan Alonso Ramírez-Fernández; Timothy F. Lawton (International Geology Review, 2025)

Enantioselective toxicity of propranolol on marine diatoms: Assessing growth, energy metabolism and oxidative damage in Phaeodactylum tricornutum - Marina Arenas; Eduardo Feijão; Irina A. Duarte; Vanessa F. Fonseca; Irene Aparicio; Esteban Alonso; Bernardo Duarte (Marine Pollution Bulletin, 2025)

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Hyperglucagonemia and glucagon hypersecretion in early type 2 diabetes result from multifaceted dysregulation of pancreatic mouse α-cells - Antonia Ruiz-Pino; Arianna Goncalves-Ramírez; Margarita Jiménez-Palomares; Beatriz Merino; Manuel Castellano-Muñoz; Jean F. Vettorazzi; Alex Rafacho; Laura Marroquí; Ángel Nadal; Paloma Alonso-Magdalena; Germán Perdomo; Irene Cózar-Castellano; et al. (Pflügers Archiv - European Journal of Physiology, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Bacterial bioaugmentation for paracetamol removal from water and sewage sludge. Genomic approaches to elucidate biodegradation pathway - A. Lara-Moreno; A. Vargas-Ordóñez; J. Villaverde; F. Madrid; J.D. Carlier; J.L. Santos; E. Alonso; E. Morillo (Journal of Hazardous Materials, 2024)

A Tropical Estuary Where Mercury Does Not Biomagnify and its Adjacent Waters that Render Extremely High Mercury Concentrations in Top Predators - Paulo R. Dorneles; Thaís de C. Paiva; Gabriel P. Bighetti; Dhoone Menezes; António M. B. Marques; Patricia S. L. Anacleto; Leonardo Flach; Fabíola H. S. Fogaça; Ana Paula C. Farro; Mariana F. Nery; Ana Lúcia Cypriano-Souza; Mirela D’arc; et al. (Archives of Environmental Contamination and Toxicology, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

LAFeBS, alive, kicking, and growing: the story continues… - R. Daniel Peluffo; Silvia del V. Alonso; Rosangela Itri; F. Luis González Flecha; Leandro Barbosa (Biophysical Reviews, 2024)

Chemical and physical properties of sewage sludge as a substrate for tree seedlings - J. M. Alonso; É. F. M. Pinheiro; L. F. de Sousa Antunes; T. da Costa Lima; J. G. Ribeiro; P. S. dos Santos Leles (International Journal of Environmental Science and Technology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Influence of meteorological variables and air pollutants on measurements from automatic pollen sampling devices - M. González-Alonso; J. Oteros; M. Widmann; J.M. Maya-Manzano; C. Skjøth; L. Grewling; D. O'Connor; M. Sofiev; F. Tummon; B. Crouzy; B. Clot; J. Buters; et al. (Science of The Total Environment, 2024)

Exposure to environmental pollutants and genetic variants related to oxidative stress and xenobiotic metabolism—Association with prostate cancer - Beatriz Álvarez-González; Antonio F. Hernández; Alberto Zafra-Gómez; Lucia Chica-Redecillas; Sergio Cuenca-López; Fernando Vázquez-Alonso; Luis Javier Martínez-González; María Jesús Álvarez-Cubero (Environmental Toxicology and Pharmacology, 2024)

Regional assessment of the historical trends of mercury in sediment cores from Wider Caribbean coastal environments - Yoelvis Bolaños-Alvarez; Ana Carolina Ruiz-Fernández; Joan-Albert Sanchez-Cabeza; Misael Díaz Asencio; Luisa F. Espinosa; Juan Pablo Parra; Jesús Garay; Ramón Delanoy; Nicolás Solares; Katia Montenegro; Alexis Peña; Fabiola López; et al. (Science of The Total Environment, 2024)

Estimation of the addition of fly ash and its environmental impact in the manufacture of cement pastes - Juan D. Alonso; Ximena Gaviria; Julián E. López; Juan F. Saldarriaga (Environment, Development and Sustainability, 2024)
The cement industry is one of those that consumes the most energy, due to the high temperatures required to produce this material, and it is also one of the most that generates high CO 2 emissions. In this work, the addition of sugarcane ash, bituminous coal and hazardous residues in cement pastes were evaluated. For this, cement pastes were produced in accordance with ASTM C305, from which the test specimens were prepared to analyze compressive strength and parallel to this, metal leaching tests were performed using the SPLP procedure. Following this, the reactivity of the fly ash in the cement pastes was evaluated by means of thermogravimetric tests. The different analyzes were carried out at the ages of 1, 3, 7, 14, 28, 56, 90 and 180 days. The ashes were characterized by XRF, XRD, and laser grain size, where the SiO 2 and Al 2 O 3 contents in the cane and bituminous coal ash were relatively high, contrary to what was obtained in the treated and untreated hazardous waste ash. These results are quite innovative because there are few works using HW in the literature. Cements with CAN, BIT, and THW5 were found to show equivalent and even superior compressive strength performance when compared to control. This work can be used as a guide and an inspiration for policymakers who want to apply this kind of material in the cement sector and promote evidence-based decisions and regulations.

The role of automatic pollen and fungal spore monitoring across major end-user domains - Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; Nicolas Bruffaerts; Jeroen Buters; Paloma Cariñanos; Sevcan Celenk; Marie Choël; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; et al. (Aerobiologia, 2024)
The advent of automatic pollen and fungal spore monitoring over the past few years has brought about a paradigm change. The provision of real-time information at high temporal resolution opens the door to a wide range of improvements in terms of the products and services made available to a widening range of end-users and stakeholders. As technology and methods mature, it is essential to properly quantify the impact automatic monitoring has on the different end-user domains to better understand the real long-term benefits to society. In this paper, we focus the main domains where such impacts are expected, using Europe as a basis to provide qualitative estimates and to describe research needs to better quantify impacts in future. This will, in part, also serve to justify further investment and help to expand monitoring networks.

Natural radionuclides as tracers of coastal sediment dynamics in El Confital Bay (Spain): Spatial distribution and relationships with sediment characteristics - A.C. Arriola-Velásquez; A. Tejera; I. Alonso; F. Cámara; M. Cantaluppi; H. Alonso; N. Miquel-Armengol; J.G. Rubiano; P. Martel (CATENA, 2024)

The role of snow in scavenging aerosol particles: A physical-chemical characterization - C. Blanco-Alegre; A.I. Calvo; A. Castro; F. Oduber; E. Alonso-Blanco; C. Alves; M. Cerqueira; R. López; F. Lucarelli; S. Nava; G. Calzolai; R. Fraile (Science of The Total Environment, 2024)

Automatic differentiation of Eucalyptus species through Sentinel-2 images, Worldview-3 images and LiDAR data - L. Alonso; A. Rodríguez-Dorna; J. Picos; F. Costas; J. Armesto (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Investigating an extreme meteo-oceanographic event in the southern Brazil from in situ observations and modeling results - Dayanis M. Borges; Humberto L. Varona; Marcelo F. Alonso; Moacyr Araujo; Fabrice Hernandez (Regional Studies in Marine Science, 2023)

Genetic variants of antioxidant and xenobiotic metabolizing enzymes and their association with prostate cancer: A meta-analysis and functional in silico analysis - Beatriz Álvarez-González; Patricia Porras-Quesada; Verónica Arenas-Rodríguez; Alba Tamayo-Gómez; Fernando Vázquez-Alonso; Luis Javier Martínez-González; Antonio F. Hernández; María Jesús Álvarez-Cubero (Science of The Total Environment, 2023)

The noble gas signature of the 2021 Tajogaite eruption (La Palma, Canary Islands) - A. Sandoval-Velasquez; A.L. Rizzo; F. Casetta; T. Ntaflos; A. Aiuppa; M. Alonso; E. Padrón; M.J. Pankhurst; A. Mundl-Petermeier; V. Zanon; N.M. Pérez (Journal of Volcanology and Geothermal Research, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Mine water as a source of energy: an application in a coalfield in Laciana Valley (León, NW Spain) - A. Matas-Escamilla; R. Álvarez; F. García-Carro; L. Álvarez-Alonso; P. Cienfuegos; J. Menéndez; A. Ordóñez (Clean Technologies and Environmental Policy, 2023)
Mine water can be a renewable and economical source of geothermal and hydraulic energy. Nine discharges from closed and flooded coal mines in the Laciana Valley (León, NW Spain) have been studied. Various technologies for the energy use of mine water, as well as the influence of factors such as temperature, the need for water treatment, investment, potential customers and expansion capacity, have been evaluated by means of a decision-making tool. It is concluded that the most advantageous option is an open-loop geothermal system using the waters of a mountain mine, the temperature of which exceeds 14 °C and whose distance to customers is less than 2 km. A technical–economic viability study for a district heating network designed to supply heating and hot water to six public buildings in the nearby town of Villablino is presented. The proposed use of mine water might help areas that have been greatly affected socioeconomically by the closure of the mines and has other advantages compared to conventional energy systems, such as the reduction of CO 2 emissions. Graphical Abstract It showing the advantages of using mine water as an energy source for district heating and a simplified layout.

Biophysical Reviews (ISSUE 4 2023): LAFeBS—highlighting biophysics in Latin America - R. Daniel Peluffo; Silvia del V. Alonso; Rosangela Itri; F. Luis González Flecha; Leandro Barbosa (Biophysical Reviews, 2023)

Fifty years of biophysics in Argentina - Silvia del V. Alonso; F. Luis González Flecha (Biophysical Reviews, 2023)

The Latin American Federation of Biophysical Societies (LAFeBS) - Silvia del Valle Alonso; Rosangela Itri; Leandro R. S. Barbosa; R. Daniel Peluffo; F. Luis González Flecha (Biophysical Reviews, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Embryonic cerebrospinal fluid influence in the subependymal neurogenic niche in adult mouse hippocampus - M. Madrigal; P. Martín; F. Lamus; J.M. Fernandez; A. Gato; MI. Alonso (Tissue and Cell, 2023)

Canarian common ravens electrocution: a post-mortem case study - A. Fernandez; P. Diaz-Santana; M. Andrada; L. Marrero; P. Alonso; F. Consoli; J. Navarro; C. Fiorito; C. Díaz-Santana (Journal of Comparative Pathology, 2023)

Planktonic foraminifera response to orbital and millennial-scale climate variability at the southern Iberian Margin (IODP Site U1385) during Marine Isotope Stages 20 and 19 - Angela Girone; Adriano De Astis; Francisco J. Sierro; Ivan Hernández-Almeida; Montserrat Alonso Garcia; Maria F. Sánchez Goñi; Patrizia Maiorano; Maria Marino; Samanta Trotta; David Hodell (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Addition of raw feedstocks and biochars to the soil on the sorption–desorption and biodegradation of 14C-saflufenacil - F. S. de Oliveira; V. Takeshita; K. F. Mendes; V. L. Tornisielo; F. G. Alonso; L. V. Junqueira; M. B. Neto; H. A. Lins; D. V. Silva (International Journal of Environmental Science and Technology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Benthic macrohabitat classification and Madracis spp. coral patch distribution in a deep-sea marine protected area of Colombia - Cristina Cedeño-Posso; Martha Vides-Casado; Venus Rocha; Giomar H. Borrero-Pérez; Andrea Polanco F; David Alonso (Frontiers in Marine Science, 2022)
Corales de Profundidad National Natural Park (CPNNP), at the central Colombian Caribbean margin, has an extension of 142.195 ha with depths ranging from 34 to 1,234 m. The CPNNP’s essential ecological value is Madracis spp. as potential structure-forming deep-water coral; this work represents the first footages of these unique habitats for the Colombian Caribbean. In 11 sectors, remote video surveys are conducted, based on a detailed digital elevation model. From these sectors, four cover mesophotic zones (46–169m depth), and seven cover aphotic zones (up to 354m depth). After still images’ description and interpretation, a guide was generated with nine types of macrohabitats surrounding the coral formations of the CPNNP: soft substrate (mud/sand), soft substrate/rubble/rock with solitary corals, coral and shell rubble, rock/ledges with attached fauna, rugged stones with attached fauna, hard substrate with attached fauna, sandstone with attached fauna, soft substrate with burrows, and pockmark with attached fauna. Video transect analysis confirms the occurrence of Madracis spp., with coral patches as the main framework builder of the CPNNP. These patches comprise many clumped 50 to 80 cm high coral colonies that developed over slow slopes, with seafloor elevations between 107 and 233 m and textured soils of soft and not very compact ridges, associated with the macrohabitat sandstone with attached fauna. This information is being used for the management and monitoring of this unique protected area.

Biophysical Reviews special issue call: LAFeBS—highlighting biophysics in Latin America - R. Daniel Peluffo; Silvia del V. Alonso; Rosangela Itri; F. Luis González Flecha; Leandro R. S. Barbosa (Biophysical Reviews, 2022)

Enhanced infiltration by trees in floodable cattle ranches in Paraguay - V. Cruz-Alonso; K. Musálem; J. Mongil-Manso; F. Viñegla; A. Insfrán; J. M. Rey-Benayas (Agroforestry Systems, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Upper Cretaceous Limestones as Stone Resources for the Monuments of Oviedo (Asturias, NW of Spain): Petrographic Variability and Stratigraphic Origin - B. González-Fernández; F. J. Alonso; L. Valdeón; L. Pando (Geoheritage, 2022)
This study offers an analysis of the petrographic variability and the stratigraphic origin of the rocks used as building stones in the vast majority of the historical monuments of Oviedo, including UNESCO World Heritage Sites. More than a hundred samples of Upper Cretaceous stone were obtained from monuments and outcrops. Based on petrographic characteristics, a macroscopic scale classification was established, and two lithotypes were identified, Piedramuelle and La Granda. Further varieties were differentiated at a microscopic scale: five in the first lithotype and two in the second one. Regarding stratigraphic origin, both rock types come from the Upper Cretaceous San Lázaro and Oviedo Formations. The building stones were mostly extracted from quarries located in the surroundings of the city and, in some cases, within the urban area. The lithotype used in monuments built up to the eighteenth century is Piedramuelle, while La Granda dominates in buildings erected during the seventeenth and eighteenth centuries.

Viability meets suitability: distribution of the extinction risk of an imperiled titi monkey (Callicebus barbarabrownae) under multiple threats - Hamilton Ferreira Barreto; Leandro Jerusalinsky; Anderson A. Eduardo; André Chein Alonso; Eduardo Marques Santos Júnior; Raone Beltrão-Mendes; Stephen F. Ferrari; Sidney F. Gouveia (International Journal of Primatology, 2022)

Descending necrotizing mediastinitis from Ludwig’s angina: a life-threatening condition - Miguel F. Carrascosa; Silvia Cayón Hoyo; Roberto Echeverría San-Sebastián; Iratxe Alcalde Díez; Sergio Tapia Concha; Sandra Campos Fernández; Eva María Alonso-Fernández; Carmen González-Carrero Sixto; David Lobo Duro; Laura Sánchez Moreno; Miguel Ángel Zabaleta-Murguiondo (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Multiple intrusion stages and mantle sources of the Paleozoic Kuznetsk Alatau alkaline province, Southern Siberia: geochemistry and Permian U–Pb, Sm–Nd ages in the Goryachegorsk ijolite-foyaite intrusion - V. V. Vrublevskii; I. F. Gertner; G. Gutiérrez-Alonso; M. Hofmann; O. M. Grinev; A. A Mustafaev (International Geology Review, 2021)

Spike architecture traits associated with type II resistance to fusarium head blight in bread wheat - M. F. Franco; G. A. Lori; G. Cendoya; M. P. Alonso; J. S. Panelo; I. Malbrán; N. E. Mirabella; A. C. Pontaroli (Euphytica, 2021)

Molecular characterization of the spectacled caiman ( Caiman crocodilus ) in the upper Magdalena River basin, Colombia: Demographic and phylogeographic insights - Diana M. Díaz-Moreno; Felipe Hernández-Gonzalez; Juan F. Moncada-Jimenez; Cristina Mora; Carlos Prada; Gonzalo Jiménez-Alonso; Sergio A. Balaguera-Reina (Systematics and Biodiversity, 2021)

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

Arsenic in Latin America: New findings on source, mobilization and mobility in human environments in 20 countries based on decadal research 2010-2020 - Jochen Bundschuh; Maria Aurora Armienta; Nury Morales-Simfors; Mohammad Ayaz Alam; Dina L. López; Valeria Delgado Quezada; Sebastian Dietrich; Jerusa Schneider; Joseline Tapia; Ondra Sracek; Elianna Castillo; Lue-Meru Marco Parra; et al. (Critical Reviews in Environmental Science and Technology, 2021)

Carboxymethyl-β-glucan/chitosan nanoparticles: new thermostable and efficient carriers for antigen delivery - Ana Sara Cordeiro; Yagmur Farsakoglu; José Crecente-Campo; María de la Fuente; Santiago F. González; María José Alonso (Drug Delivery and Translational Research, 2021)

Methodology for flushing pressurised irrigation networks for fertigation and operation maintenance purposes - M. A. Jiménez-Bello; J. C. Alonso Campos; J. Manzano-Juárez; F. Martínez Alzamora (Irrigation Science, 2021)

High versus standard doses of corticosteroids in severe COVID-19: a retrospective cohort study - Enric Monreal; Susana Sainz de la Maza; Elena Natera-Villalba; Álvaro Beltrán-Corbellini; Fernando Rodríguez-Jorge; Jose Ignacio Fernández-Velasco; Paulette Walo-Delgado; Alfonso Muriel; Javier Zamora; Araceli Alonso-Canovas; Jesús Fortún; Luis Manzano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Vineyard environments influence Malbec grapevine phenotypic traits and DNA methylation patterns in a clone-dependent way - Anabella Varela; Verónica N. Ibañez; Rodrigo Alonso; Diego Zavallo; Sebastián Asurmendi; Sebastián Gomez Talquenca; Carlos F. Marfil; Federico J. Berli (Plant Cell Reports, 2021)

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Landscape factors modulating patterns of salmonid distribution during summer in north Patagonian rivers - Mailén E. Lallement; Magalí Rechencq; María V. Fernández; Eduardo Zattara; Alejandro Sosnovsky; Pablo Vigliano; Gilda Garibotti; Marcelo F. Alonso; Gustavo Lippolt; Patricio J. Macchi (Journal of Fish Biology, 2020)
Understanding how ecosystem processes influencing fish distribution operate across spatial scales is important to understand biological invasions. Salmonids, originally from the Northern Hemisphere, have been repeatedly introduced throughout the world, making them an ideal group to test hypotheses about factors driving invasions. We assessed the influence of environmental variables at the watershed scale on the abundance and structure of salmonid assemblages in the breeding streams of the Upper Limay river basin, Rio Negro, Argentina. We combined field captures with digital map data and geographic information systems to examine landscape‐level patterns of salmonid abundance in 35 representative sub‐basins of the environmental gradient. We employed a hierarchical cluster analysis and classification and regression tree models to relate the abundance of salmonids and types of species assemblages with environmental characteristics at watershed level. We found stream localization, precipitation regime, altitude and air temperature to be important predictors of the abundance and assemblage structure of salmonids. Total catches showed an increasing gradient of catch‐per‐unit‐effort from west to east and from north to south, with Oncorhynchus mykiss being the most abundant species. O. mykiss relative abundance was westward skewed, where smaller catchments with steeper and shaded valleys are drained by less productive streams with more irregular hydrological regimes, like those found in this species' North American native range. In contrast, the abundance of Salmo trutta abundance was eastward skewed, where larger, sunnier and more gently sloped catchments result in more productive streams with stable hydrological regimes, like those found in that species' European native range. Thus, differential salmonid abundance could result from the interplay between the evolutionary fingerprint left by each species' native environment (especially flow and temperature regimes) and the availability of those conditions in new environments to which they have been translocated. By furthering our understanding of how landscape conditioned invasion success, these findings can help guide the management of economically important introduced fish.

Effect of the mother tree age and acorn weight in the regenerative characteristics of Quercus faginea - I. M. Alonso-Crespo; F. Silla; P. Jiménez del Nogal; M. J. Fernández; C. Martínez-Ruiz; B. Fernández-Santos (European Journal of Forest Research, 2020)

Plant community shifts along tree canopy cover gradients in grazed Patagonian Nothofagus antarctica forests and grasslands - Máximo F. Alonso; Hope Wentzel; Andreas Schmidt; Oscar Balocchi (Agroforestry Systems, 2020)

Passive sampling as a feasible tool for mapping and model evaluation of the spatial distribution of nitrogen oxides in the city of Curitiba, Brazil - Erika Felix; Lars Gidhagen; Marcelo F. Alonso; Everaldo P. Nahirny; Bruno L. Alves; David Segersson; Jorge H. Amorim (Air Quality, Atmosphere & Health, 2019)

Numerical characterization of torrential floods in the plain of Saïdia (North-East of Morocco) - A. Grari; M. Chourak; F. Boushaba; S. Cherif; E. García Alonso (Arabian Journal of Geosciences, 2019)

Empirical selection between least‐cost and current‐flow designs for establishing wildlife corridors in Gabon - Hadrien P. A. Vanthomme; Brave S. Nzamba; Alfonso Alonso; Angelique F. Todd (Conservation Biology, 2019)
Corridors are intended to increase species survival by abating landscape fragmentation resulting from the conversion of natural habitats into human‐dominated matrices. Conservation scientists often rely on 1 type of corridor model, typically the least‐cost model or current‐flow model, to construct a linkage design, and their choice is not usually based on theory or empirical evidence. We developed a method to empirically confirm whether corridors produced by these 2 models are used by target species under current landscape conditions. We applied this method in the Gamba landscape between 2 national parks in southwestern Gabon. We collected signs of presence of African forest elephant ( Loxodonta cyclotis ), forest buffalo ( Syncerus caffer nanus ), and 2 apes, western lowland gorilla ( Gorilla gorilla gorilla ) and central chimpanzee ( Pan troglodytes troglodytes ), on transects. We used patch‐occupancy models to identify least‐cost and current‐flow corridors for these 4 species. On average, 28.7% of current‐flow corridors overlapped with least‐cost corridors, confirming that the choice of corridor model can affect the location of the resulting linkage design. We validated these corridors by monitoring signs and examining camera detections on new transects within and outside modeled corridors. Current‐flow corridors performed better than least‐cost corridors for elephants, whereas the opposite was found for buffalo and apes. Locations of the highest priority corridors for the 3 taxa did not overlap, and only 18.3% of their combined surface was common among 2 species. We used centrality metrics to calculate the average contribution of corridor pixels to landscape connectivity and derived an index that can be used to prioritize corridors. As a result, we recommend protecting at least 17.4% of the land surface area around Gamba town to preserve the preferred travel routes of the target species.

Air and wet bulb temperature lapse rates and their impact on snowmaking in a Pyrenean ski resort - Juan Ignacio López-Moreno; F. Navarro-Serrano; C. Azorín-Molina; P. Sánchez-Navarrete; E. Alonso-González; I. Rico; E. Morán-Tejeda; S. Buisan; J. Revuelto; M. Pons; S.M. Vicente-Serrano (Theoretical and Applied Climatology, 2019)

Beyond the Last Glacial Maximum: Island endemism is best explained by long‐lasting archipelago configurations - Sietze J. Norder; Konstantinos Proios; Robert J. Whittaker; María R. Alonso; Paulo A. V. Borges; Michael K. Borregaard; Robert H. Cowie; F. B. Vincent Florens; António M. de Frias Martins; Miguel Ibáñez; W. Daniel Kissling; Lea de Nascimento; et al. (Global Ecology and Biogeography, 2019)
Aim To quantify the influence of past archipelago configuration on present‐day insular biodiversity patterns, and to compare the role of long‐lasting archipelago configurations over the Pleistocene to configurations of short duration such as at the Last Glacial Maximum (LGM) and the present‐day. Location 53 volcanic oceanic islands from 12 archipelagos worldwide—Azores, Canary Islands, Cook Islands, Galápagos, Gulf of Guinea, Hawaii, Madeira, Mascarenes, Pitcairn, Revillagigedo, Samoan Islands and Tristan da Cunha. Time period The last 800 kyr, representing the nine most recent glacial–interglacial cycles. Major taxa studied Land snails and angiosperms. Methods Species richness data for land snails and angiosperms were compiled from existing literature and species checklists. We reconstructed archipelago configurations at the following sea levels: the present‐day high interglacial sea level, the intermediate sea levels that are representative of the Pleistocene and the low sea levels of the LGM. We fitted two alternative linear mixed models for each archipelago configuration using the number of single‐island endemic, multiple‐island endemic and (non‐endemic) native species as a response. Model performance was assessed based on the goodness‐of‐fit of the full model, the variance explained by archipelago configuration and model parsimony. Results Single‐island endemic richness in both taxonomic groups was best explained by intermediate palaeo‐configuration (positively by area change, and negatively by palaeo‐connectedness), whereas non‐endemic native species richness was poorly explained by palaeo‐configuration. Single‐island endemic richness was better explained by intermediate archipelago configurations than by the archipelago configurations of the LGM or present‐day. Main conclusions Archipelago configurations at intermediate sea levels—which are representative of the Pleistocene—have left a stronger imprint on single‐island endemic richness patterns on volcanic oceanic islands than extreme archipelago configurations that persisted for only a few thousand years (such as the LGM). In understanding ecological and evolutionary dynamics of insular biota it is essential to consider longer‐lasting environmental conditions, rather than extreme situations alone.

Mannheimia haemolytica OmpP2-like is an amyloid-like protein, forms filaments, takes part in cell adhesion and is part of biofilms - J. F. Montes García; Sergio Vaca; Norma L. Delgado; Alina Uribe-García; Candelario Vázquez; P. Sánchez Alonso; J. Xicohtencatl Cortes; A. Cruz Cordoba; E. Negrete Abascal (Antonie van Leeuwenhoek, 2018)

Comparison of Nanoscale Zero-Valent Iron, Compost, and Phosphate for Pb Immobilization in an Acidic Soil - M. Gil-Díaz; L. F. López; J. Alonso; M. C. Lobo (Water, Air, & Soil Pollution, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Summer-autumn air pollution in León, Spain: changes in aerosol size distribution and expected effects on the respiratory tract - F. Oduber; A. Castro; A.I. Calvo; C. Blanco-Alegre; E. Alonso-Blanco; P. Belmonte; R. Fraile (Air Quality, Atmosphere & Health, 2018)

Estimation of near‐surface air temperature lapse rates over continental Spain and its mountain areas - F. Navarro‐Serrano; J. I. López‐Moreno; C. Azorin‐Molina; E. Alonso‐González; M. Tomás‐Burguera; A. Sanmiguel‐Vallelado; J. Revuelto; S. M. Vicente‐Serrano (International Journal of Climatology, 2018)
Although the mean environmental lapse rate (MELR) value (a linear decrease of − 6.5 °C/km) is the most widely used, near‐surface (i.e., non‐free atmosphere) air temperature lapse rates (NSLRs; measured at ~1.5 m height) are variable in space and time because of their dependence on topography and meteorological conditions. In this study we conducted the first analysis of the spatial and temporal variability of NSLRs for continental Spain and their relationship to synoptic atmospheric circulation (circulation weather types [CWTs]), focusing on major mountain areas including the Pyrenees, Cantabrian, Central, Baetic, and Iberian ranges. The results showed that the NSLR varied markedly at spatial and seasonal scales and depended on the dominant atmospheric conditions. The median NSLR values were weaker (less negative) than the MELR for the mountain areas (Pyrenees −5.17 °C/km; Cantabrian range −5.22 °C/km; Central range −5.78 °C/km; Baetic range −4.83 °C/km; Iberian range −5.79 °C/km) and for the entire continental Spain (−5.28 °C/km). For the entire continental Spain the steepest NSLR values were found in April (−5.80 °C/km), May (−5.58 °C/km), and October (−5.54 °C/km) because of the dominance of northerly and westerly advections of cold air. The weakest NSLR values were found in July (−4.67 °C/km) and August (−4.78 °C/km) because of the inland heating, and in winter because of the occurrence of thermal inversions. As the use of the MELR involves the assumption of large errors, we propose 1 zonal, 12 monthly, 11 CWTs, and 132 hybrid monthly–CWTs NSLRs for each of the mountain ranges and for the entire continental Spain. More regional studies are urgently needed to accurately assess the NSLR as a function of atmospheric circulation conditions.

Crustal melting and recycling: geochronology and sources of Variscan syn-kinematic anatectic granitoids of the Tormes Dome (Central Iberian Zone). A U–Pb LA-ICP-MS study - F. J. López-Moro; M. López-Plaza; G. Gutiérrez-Alonso; J. Fernández-Suárez; A. López-Carmona; M. Hofmann; R. L. Romer (International Journal of Earth Sciences, 2018)

Can Empirical Algorithms Successfully Estimate Aragonite Saturation State in the Subpolar North Atlantic? - Daniela Turk; Michael Dowd; Siv K. Lauvset; Jannes Koelling; Fernando Alonso-Pérez; Fiz F. Pérez (Frontiers in Marine Science, 2017)

Ecological plant epigenetics: Evidence from model and non‐model species, and the way forward - Christina L. Richards; Conchita Alonso; Claude Becker; Oliver Bossdorf; Etienne Bucher; Maria Colomé‐Tatché; Walter Durka; Jan Engelhardt; Bence Gaspar; Andreas Gogol‐Döring; Ivo Grosse; Thomas P. van Gurp; et al. (Ecology Letters, 2017)
Growing evidence shows that epigenetic mechanisms contribute to complex traits, with implications across many fields of biology. In plant ecology, recent studies have attempted to merge ecological experiments with epigenetic analyses to elucidate the contribution of epigenetics to plant phenotypes, stress responses, adaptation to habitat, and range distributions. While there has been some progress in revealing the role of epigenetics in ecological processes, studies with non‐model species have so far been limited to describing broad patterns based on anonymous markers of DNA methylation. In contrast, studies with model species have benefited from powerful genomic resources , which contribute to a more mechanistic understanding but have limited ecological realism. Understanding the significance of epigenetics for plant ecology requires increased transfer of knowledge and methods from model species research to genomes of evolutionarily divergent species, and examination of responses to complex natural environments at a more mechanistic level. This requires transforming genomics tools specifically for studying non‐model species, which is challenging given the large and often polyploid genomes of plants. Collaboration among molecular geneticists, ecologists and bioinformaticians promises to enhance our understanding of the mutual links between genome function and ecological processes.

Perceptions of rodent-associated problems: an experience in urban and rural areas of Yucatan, Mexico - Jesús Alonso Panti-May; Lorenzo Sodá-Tamayo; Naivy Gamboa-Tec; Rosy Cetina-Franco; Nohemi Cigarroa-Toledo; Carlos Machaín-Williams; María del Rosario Robles; Silvia F. Hernández-Betancourt (Urban Ecosystems, 2017)

Evolution of the corpus luteum volume determined ultrasonographically and its relation to the plasma progesterone concentration after artificial insemination in pregnant and non-pregnant dairy cows - C. Gómez-Seco; B. Alegre; F. Martínez-Pastor; J. G. Prieto; J. R. González-Montaña; M. E. Alonso; J. C. Domínguez (Veterinary Research Communications, 2017)

New evidence of bones used as fuel in the Gravettian level at Coímbre cave, northern Iberian Peninsula - José Yravedra; David Álvarez-Alonso; Verónica Estaca-Gómez; Pablo López-Cisneros; Álvaro Arrizabalaga; Mikelo Elorza; Ma. José Iriarte; Jesús F. Jordá Pardo; Carmen Sesé; Paloma Uzquiano (Archaeological and Anthropological Sciences, 2017)

Isolated theropod teeth associated with sauropod remains from El Oterillo II (Early Cretaceous) site of Salas de los Infantes (Burgos, Spain) - A. Alonso; J. I. Canudo; F. Torcida Fernández-Baldor; P. Huerta (Journal of Iberian Geology, 2017)

Antipoaching standards in onshore hydrocarbon concessions drawn from a Central African case study - Hadrien P.A. Vanthomme; Elie Tobi; Angelique F. Todd; Lisa Korte; Alfonso Alonso (Conservation Biology, 2017)
Unsustainable hunting outside protected areas is threatening tropical biodiversity worldwide and requires conservationists to engage increasingly in antipoaching activities. Following the example of ecocertified logging companies, we argue that other extractive industries managing large concessions should engage in antipoaching activities as part of their environmental management plans. Onshore hydrocarbon concessions should also adopt antipoaching protocols as a standard because they represent a biodiversity threat comparable to logging. We examined the spatiotemporal patterns of small‐ and large‐mammal poaching in an onshore oil concession in Gabon, Central Africa, with a Bayesian occupancy model based on signs of poaching collected from 2010 to 2015 on antipoaching patrols. Patrol locations were initially determined based on local intelligence and past patrol successes (adaptive management) and subsequently with a systematic sampling of the concession. We generated maps of poaching probability in the concession and determined the temporal trends of this threat over 5 years. The spatiotemporal patterns of large‐ and small‐mammal poaching differed throughout the concession, and likely these groups will need different management strategies. By elucidating the relationship between site‐specific sampling effort and detection probability, the Bayesian method allowed us to set goals for future antipoaching patrols. Our results indicate that a combination of systematic sampling and adaptive management data is necessary to infer spatiotemporal patterns with the statistical method we used. On the basis of our case study, we recommend hydrocarbon companies interested in implementing efficient antipoaching activities in their onshore concessions to lay the foundation of long‐needed industry standards by: adequately measuring antipoaching effort; mixing adaptive management and balanced sampling; setting goals for antipoaching effort; pairing patrols with large‐mammal monitoring; supporting antipoaching patrols across the landscape; restricting access to their concessions; performing random searches for bushmeat and mammal products at points of entry; controlling urban and agricultural expansion; supporting bushmeat alternatives; and supporting land‐use planning.

Increased Expression of Brain-Derived Neurotrophic Factor Transcripts I and VI, cAMP Response Element Binding, and Glucocorticoid Receptor in the Cortex of Patients with Temporal Lobe Epilepsy - G. A. Martínez-Levy; L. Rocha; F. Rodríguez-Pineda; M. A. Alonso-Vanegas; A. Nani; R. M. Buentello-García; M. Briones-Velasco; D. San-Juan; J. Cienfuegos; C. S. Cruz-Fuentes (Molecular Neurobiology, 2017)

Modelling and management options for salmonid sport fisheries: A case study from Patagonia, Argentina - M. Rechencq; P. H. Vigliano; G. E. Lippolt; M. F. Alonso; P. J. Macchi; P. A. Alvear; V. Hougham; M. A. Denegri; G. Blasetti; R. Juncos; M. V. Fernandez; M. E. Lallement; et al. (Fisheries Management and Ecology, 2017)
Salmonid sport fishery management in Argentinian Patagonia is usually guided by stakeholder perceptions, which do not consider the biological and ecological constraints acting upon aquatic resources. An example of this are management policies for Traful Lake, where Atlantic salmon, Salmo salar L., was actively stocked during the last decade in an attempt to change the fish assemblage structure and to create a highly valuable sport fishery. This study assesses the likelihood of these policies achieving such assemblage structure changes through the study of affluent‐stream suitability as spawning and breeding grounds, lake fish assemblage parameters, trophic diversity and possible competition due to diet overlap. This study also assesses alternative management practices through population simulations and bioenergetic modelling under diverse catch‐size limit scenarios. This study concludes that it is not advisable to try to generate a unique and distinctive sport fishery by stocking Atlantic salmon in an already renowned fishery in Northern Patagonia. Instead, a more comprehensive framework for decision‐making is suggested, involving short‐term studies that go beyond the specific problem of the target species and incorporate the whole fish assemblage using diverse approaches and modelling strategies.

The white-clawed crayfish in Spain—reply to Clavero and Centeno-Cuadros - B. Matallanas; M. D. Ochando; F. Alonso; C. Callejas (Organisms Diversity & Evolution, 2016)

Bloodstream infections caused by Escherichia coli producing AmpC β-lactamases: epidemiology and clinical features - V. Pascual; N. Alonso; M. Simó; G. Ortiz; M. C. Garcia; M. Xercavins; A. Rivera; M. A. Morera; E. Miró; E. Espejo; F. Navarro; M. Gurguí; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Neurofeedback training with a motor imagery-based BCI: neurocognitive improvements and EEG changes in the elderly - Javier Gomez-Pilar; Rebeca Corralejo; Luis F. Nicolas-Alonso; Daniel Álvarez; Roberto Hornero (Medical & Biological Engineering & Computing, 2016)

Crustal Architecture at the Collision Zone Between Rivera and North American Plates at the Jalisco Block: Tsujal Project - Juanjo Dañobeitia; Rafael Bartolomé; Manel Prada; Francisco Nuñez-Cornú; Diego Córdoba; William L. Bandy; F. Estrada; Alejandra L. Cameselle; Diana Nuñez; Arturo Castellón; José Luis Alonso; Carlos Mortera; et al. (Pure and Applied Geophysics, 2016)

Neuroprotective Effect of the Novel Compound ITH33/IQM9.21 Against Oxidative Stress and Na+ and Ca2+ Overload in Motor Neuron-like NSC-34 Cells - Ana J. Moreno-Ortega; Lamiaa Mouhid Al-achbili; Elba Alonso; Cristóbal de los Ríos; Antonio G. García; Ana Ruiz-Nuño; María F. Cano-Abad (Neurotoxicity Research, 2016)

Discordance between morphological and taxonomic diversity: land snails of oceanic archipelagos - Kostas A. Triantis; François Rigal; Christine E. Parent; Robert A. D. Cameron; Bernd Lenzner; Aristeidis Parmakelis; Norine W. Yeung; María R. Alonso; Miguel Ibáñez; António M. de Frias Martins; Dinarte N. F. Teixeira; Owen L. Griffiths; et al. (Journal of Biogeography, 2016)
Aim Morphological and taxonomic diversity are intuitive measures of biological diversity. Previous studies have shown discordance between these measures at large spatial and temporal scales, but the implications of this pattern for the underlying processes are not understood. Using oceanic archipelagos as spatial units, we examine potential links between the morphological and taxonomic diversity of their land snail faunas in a biogeographical framework. Location Eleven major oceanic archipelagos. Methods For each archipelago, we assembled lists of indigenous land snail species, classified by family and genus, with shell height and width for each species (1723 species in total). We used biogeographic and climatic variables as potential predictors of diversity patterns. We employed regression analyses to evaluate (1) whether morphological diversity scales with taxonomic diversity at the species, genus or family level, and (2) whether morphological and taxonomic diversity correlate similarly with biogeographic/climatic factors. We also assessed which taxonomic level contributes most to morphological variation within archipelagos. Results Morphological diversity across archipelagos was strongly related to genus but not species richness. Within archipelagos, morphological variation reflected differences among genera and families but not species. Species richness was best explained by archipelago area, but morphological diversity was not significantly related to any of the physical features of archipelagos. Main conclusions Across archipelagos, species richness and morphological diversity of land snail faunas are decoupled. The relationship between species richness and the available ecological space (captured mainly by area) indicates the prevalence of niche‐based processes while, for morphological diversity, the strong conservatism of morphology at the genus level suggests the presence of diversification‐based limits. Assuming genera effectively reflect diversification, our findings indicate that morphological space on oceanic archipelagos depends primarily on the number of evolutionary units that have colonized and/or diversified through time.

Update of genetic information for the white-clawed crayfish in Spain, with new insights into its population genetics and origin - B. Matallanas; M. D. Ochando; F. Alonso; C. Callejas (Organisms Diversity & Evolution, 2016)

Influence of Mussel Culture on the Vertical Export of Phytoplankton Carbon in a Coastal Upwelling Embayment (Ría de Vigo, NW Iberia) - M. Froján; F. G. Figueiras; D. Zúñiga; F. Alonso-Pérez; B. Arbones; C. G. Castro (Estuaries and Coasts, 2016)

The macroecology of infectious diseases: a new perspective on global‐scale drivers of pathogen distributions and impacts - Patrick R. Stephens; Sonia Altizer; Katherine F. Smith; A. Alonso Aguirre; James H. Brown; Sarah A. Budischak; James E. Byers; Tad A. Dallas; T. Jonathan Davies; John M. Drake; Vanessa O. Ezenwa; Maxwell J. Farrell; et al. (Ecology Letters, 2016)
Identifying drivers of infectious disease patterns and impacts at the broadest scales of organisation is one of the most crucial challenges for modern science, yet answers to many fundamental questions remain elusive. These include what factors commonly facilitate transmission of pathogens to novel host species, what drives variation in immune investment among host species, and more generally what drives global patterns of parasite diversity and distribution? Here we consider how the perspectives and tools of macroecology, a field that investigates patterns and processes at broad spatial, temporal and taxonomic scales, are expanding scientific understanding of global infectious disease ecology. In particular, emerging approaches are providing new insights about scaling properties across all living taxa, and new strategies for mapping pathogen biodiversity and infection risk. Ultimately, macroecology is establishing a framework to more accurately predict global patterns of infectious disease distribution and emergence.

Addition of vasopressin synthetic analogue [V4Q5]dDAVP to standard chemotherapy enhances tumour growth inhibition and impairs metastatic spread in aggressive breast tumour models - Juan Garona; Marina Pifano; Maria B. Pastrian; Daniel E. Gomez; Giselle V. Ripoll; Daniel F. Alonso (Clinical & Experimental Metastasis, 2016)

Reconstructing ancient Mediterranean crossroads in Deronectes diving beetles - David García‐Vázquez; David T. Bilton; Rocío Alonso; Cesar J. Benetti; Josefina Garrido; Luis F. Valladares; Ignacio Ribera (Journal of Biogeography, 2016)
Aim To reconstruct the evolutionary history of a genus of freshwater beetle with a pan‐Mediterranean distribution, to test classic hypotheses which proposed a Miocene origin for groups with high biodiversity in the Iberian and Anatolian peninsulas. Location Mediterranean basin. Methods We sequenced four mitochondrial and one nuclear gene from 51 specimens of 30 of the c . 60 extant species of Deronectes (Dytiscidae), all typical of mid‐mountain streams from North Africa and Iberia over most of Europe to the Middle East. We used maximum likelihood, Bayesian probabilities with an a priori evolutionary rate and a dispersal–extinction–cladogenesis model to reconstruct their biogeographical history. Results Deronectes has two major lineages which originated in the mid Miocene; one including mostly eastern and another mainly western and central Mediterranean species. From these two areas, range expansions, mainly at the end of the Miocene and beginning of the Pliocene, resulted in the many species groups and some of the extant species of the genus. Most of the current diversity and distributions are, however, of Plio‐Pleistocene origin, particularly in widespread European species. Main conclusions In line with traditional hypotheses, we found an ancient division between eastern and western Mediterranean lineages of Deronectes , likely resulting from the isolation of Europe west of the Alps from the Balkans and Anatolia during the early‐middle Miocene. The history of the genus was strongly influenced by major geological and climatic events, with successive cycles of fragmentation and subsequent eastward and westward range expansions, resulting in a steady accumulation of species across the basin. Most of these range movements took place through the north side of the Mediterranean, with only local displacements in the south during the Messinian salinity crisis and a recent (Pleistocene) colonization of the Italian Peninsula, which remained largely submerged through most of the genus’ evolutionary history.

Exploring the Capacity of Water Framework Directive Indices to Assess Ecosystem Services in Fluvial and Riparian Systems: Towards a Second Implementation Phase - M. R. Vidal-Abarca; F. Santos-Martín; B. Martín-López; M. M. Sánchez-Montoya; M. L. Suárez Alonso (Environmental Management, 2016)

Effects of an environmentally relevant concentration of diuron on oyster genitors during gametogenesis: responses of early molecular and cellular markers and physiological impacts - F. Akcha; A. Barranger; E. Bachère; C. Heude Berthelin; D. Piquemal; P. Alonso; R. Rondon Sallan; G. Dimastrogiovanni; C. Porte; D. Menard; A. Szczybelski; A. Benabdelmouna; et al. (Environmental Science and Pollution Research, 2016)

First record of the genus Jenynsia from marine water on the coast of Punta del Este, Maldonado, Uruguay (Cyprinodontiformes: Anablepidae) - P. Calviño; F. Alonso (Journal of Fish Biology, 2016)
The first report of the genus Jenynsia occurring in marine waters is presented here. The evolution of high salinity tolerance within Anablepidae is discussed and a hypothesis is proposed that this characteristic is a plesiomorphic trait in Jenynsia which was probably present in the common ancestor of the Anablepidae.

Relating Hyperspectral Airborne Data to Ground Measurements in a Complex and Discontinuous Canopy - Javier F. Calleja; Christine Hellmann; Gorka Mendiguren; Suvarna Punalekar; Juanjo Peón; Alasdair MacArthur; Luis Alonso (Acta Geophysica, 2015)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Differences between endocarditis caused by Streptococcus bovis and Enterococcus spp. and their association with colorectal cancer - J. Corredoira; M. J. García-País; A. Coira; R. Rabuñal; F. García-Garrote; J. Pita; A. Rodríguez-Macías; M. Blanco; L. Lopez-Roses; M.J. López-Álvarez; M. P. Alonso-García (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Proposal for new EU habitats associated with coastal dune fields of the Macaronesian region. A case study in the Canary Islands (Spain) - Antonio I. Hernández-Cordero; F. Javier Gracia Prieto; Luis Hernández-Calvento; Emma Pérez-Chacón Espino; Ignacio Alonso (Journal of Coastal Conservation, 2015)

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

3-Indol carboxaldehyde, an imidazole synthesized from naphthoquinone β-lapachone downregulates Candida albicans biofilm - José Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Camila A. dos Anjos; Rafaela S. Santana; Ariadne Nunes Alonso; Maria Teresa Vilela Romanos; Kelly C. G. de Moura; Paula Fernandes Carneiro; Maristela Barbosa Portela; Maria do Carmo F. R. Pinto; Rosangela Maria de Araújo Soares (Medicinal Chemistry Research, 2015)

ASIC2 is present in human mechanosensory neurons of the dorsal root ganglia and in mechanoreceptors of the glabrous skin - R. Cabo; P. Alonso; E. Viña; G. Vázquez; A. Gago; J. Feito; F. J. Pérez-Moltó; O. García-Suárez; J. A. Vega (Histochemistry and Cell Biology, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

A P300-based brain–computer interface aimed at operating electronic devices at home for severely disabled people - Rebeca Corralejo; Luis F. Nicolás-Alonso; Daniel Álvarez; Roberto Hornero (Medical & Biological Engineering & Computing, 2014)

Defective autophagy impairs ATF3 activity and worsens lung injury during endotoxemia - Alina Aguirre; Inés López-Alonso; Adrián González-López; Laura Amado-Rodríguez; Estefanía Batalla-Solís; Aurora Astudillo; Jorge Blázquez-Prieto; Alvaro F. Fernández; José A. Galván; Claudia C. dos Santos; Guillermo M. Albaiceta (Journal of Molecular Medicine, 2014)

Diversity and pathogenicity of Colletotrichum species isolated from soursop in Colombia - Elizabeth Álvarez; Lederson Gañán; Alberto Rojas-Triviño; Juan F. Mejía; Germán A. Llano; Alonso González (European Journal of Plant Pathology, 2014)

Is colonoscopy necessary in cases of infection by Streptococcus bovis biotype II? - J. C. Corredoira; M. P. Alonso; M. J. García-País; R. Rabuñal; F. García-Garrote; L. López-Roses; A. Lancho; A. Coira; J. Pita; D. Velasco; M. J. López-Álvarez; H. Tjalsma; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Using Genetic Profiles of African Forest Elephants to Infer Population Structure, Movements, and Habitat Use in a Conservation and Development Landscape in Gabon - L. S. EGGERT; R. BUIJ; M. E. LEE; P. CAMPBELL; F. DALLMEIER; R. C. FLEISCHER; A. ALONSO; J. E. MALDONADO (Conservation Biology, 2014)
Conservation of wide‐ranging species, such as the African forest elephant ( Loxodonta cyclotis ), depends on fully protected areas and multiple‐use areas (MUA) that provide habitat connectivity. In the Gamba Complex of Protected Areas in Gabon, which includes 2 national parks separated by a MUA containing energy and forestry concessions, we studied forest elephants to evaluate the importance of the MUA to wide‐ranging species. We extracted DNA from elephant dung samples and used genetic information to identify over 500 individuals in the MUA and the parks. We then examined patterns of nuclear microsatellites and mitochondrial control‐region sequences to infer population structure, movement patterns, and habitat use by age and sex. Population structure was weak but significant, and differentiation was more pronounced during the wet season. Within the MUA, males were more strongly associated with open habitats, such as wetlands and savannas, than females during the dry season. Many of the movements detected within and between seasons involved the wetlands and bordering lagoons. Our results suggest that the MUA provides year‐round habitat for some elephants and additional habitat for others whose primary range is in the parks. With the continuing loss of roadless wilderness areas in Central Africa, well‐managed MUAs will likely be important to the conservation of wide‐ranging species. Utilización de Perfiles Genéticos de Elefantes Africanos para Inferir su Estructura Poblacional, Movimientos y Uso del Hábitat en un Paisaje con Conservación y Desarrollo en Gabón Resumenfgs

Phylogeography of the white-clawed crayfish (Austropotamobius italicus) in Spain: inferences from microsatellite markers - B. Matallanas; M. D. Ochando; F. Alonso; C. Callejas (Molecular Biology Reports, 2013)

On the dependence of ENSO simulation on the coupled model mean state - L. Magnusson; M. Alonso-Balmaseda; F. Molteni (Climate Dynamics, 2013)

Mercury, methylmercury, and selenium in blood of bird species from Doñana National Park (Southwestern Spain) after a mining accident - C. Rodríguez Alvárez; M. Jiménez Moreno; L. López Alonso; B. Gómara; F. J. Guzmán Bernardo; R. C. Rodríguez Martín-Doimeadios; M. J. González (Environmental Science and Pollution Research, 2013)

Support Vector Machines and Multilayer Perceptron Networks Used to Evaluate the Cyanotoxins Presence from Experimental Cyanobacteria Concentrations in the Trasona Reservoir (Northern Spain) - J. A. Vilán Vilán; J. R. Alonso Fernández; P. J. García Nieto; F. Sánchez Lasheras; F. J. de Cos Juez; C. Díaz Muñiz (Water Resources Management, 2013)

Fungal infection in cerebrospinal fluid from some patients with multiple sclerosis - D. Pisa; R. Alonso; F. J. Jiménez-Jiménez; L. Carrasco (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Study of the impact of wildfire emissions, through MOPITT total CO column, at different spatial scales - A. Calle; P. Salvador; F. González-Alonso (International Journal of Remote Sensing, 2013)

Ecotoxicity Bioassays on Leachates from Poultry Manure - M. Delgado; R. Miralles de Imperial; F. Alonso; C. Rodríguez; J. V. Martín (Bulletin of Environmental Contamination and Toxicology, 2013)

Population stratification may bias analysis of PGC-1α as a modifier of age at Huntington disease motor onset - Eliana Marisa Ramos; Jeanne C. Latourelle; Ji-Hyun Lee; Tammy Gillis; Jayalakshmi S. Mysore; Ferdinando Squitieri; Alba Di Pardo; Stefano Di Donato; Michael R. Hayden; Patrick J. Morrison; Martha Nance; Christopher A. Ross; et al. (Human Genetics, 2012)

Score to identify the severity of adult patients with influenza A (H1N1) 2009 virus infection at hospital admission - A. Capelastegui; J. M. Quintana; A. Bilbao; P. P. España; O. Garin; J. Alonso; J. Astray; R. Cantón; J. Castilla; A. Castro; M. Delgado-Rodríguez; P. Godoy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Cross-conditional entropy and coherence analysis of pharmaco-EEG changes induced by alprazolam - J. F. Alonso; M. A. Mañanas; S. Romero; M. Rojas-Martínez; J. Riba (Psychopharmacology, 2012)

Kilometre-scale sheath folds in the western Betics (south of Spain) - M. Orozco; F. M. Alonso-Chaves (International Journal of Earth Sciences, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Procedures for Controlling the Size, Structure and Optical Properties of CdS Quantum Dots during Synthesis in Aqueous Solution - María-Jesús Almendral-Parra; Ángel Alonso-Mateos; Sara Sánchez-Paradinas; Juán F. Boyero-Benito; Emilio Rodríguez-Fernández; Julio J. Criado-Talavera (Journal of Fluorescence, 2012)

Okadaic acid and dinophysis toxin 2 have differential toxicological effects in hepatic cell lines inducing cell cycle arrest, at G0/G1 or G2/M with aberrant mitosis depending on the cell line - J. A. Rubiolo; H. López-Alonso; F. V. Vega; M. R. Vieytes; L. M. Botana (Archives of Toxicology, 2011)

CIGB-300, a synthetic peptide-based drug that targets the CK2 phosphoaceptor domain. Translational and clinical research - Silvio E. Perea; Idania Baladron; Yanelda Garcia; Yasser Perera; Adlin Lopez; Jorge L. Soriano; Noyde Batista; Aley Palau; Ignacio Hernández; Hernán Farina; Idrian Garcia; Lidia Gonzalez; et al. (Molecular and Cellular Biochemistry, 2011)

The Baraza Slide: model and dynamics - D. Casas; G. Ercilla; M. Yenes; F. Estrada; B. Alonso; M. García; L. Somoza (Marine Geophysical Research, 2011)

Beyond nature: The management of a productive cultural landscape in Las Médulas area (El Bierzo, León, Spain) during pre-Roman and Roman times - L. López-Merino; L. Peña-Chocarro; M. Ruiz-Alonso; J. A. LópeZ-Sáez; F. J. Sánchez-Palencia (Plant Biosystems, 2010)

Mercury in Cultured Oysters (Crassostrea gigas Thunberg, 1793 and C. corteziensis Hertlein, 1951) from Four Coastal Lagoons of the SE Gulf of California, Mexico - C. C. Osuna-Martínez; F. Páez-Osuna; R. Alonso-Rodríguez (Bulletin of Environmental Contamination and Toxicology, 2010)

Recommendations to improve identification of hereditary and familial colorectal cancer in Europe - H. F. A. Vasen; G. Möslein; A. Alonso; S. Aretz; I. Bernstein; L. Bertario; I. Blanco; S. Bulow; J. Burn; G. Capella; C. Colas; C. Engel; et al. (Familial Cancer, 2010)

Variability comparisons for some mixture models with stochastic environments in biosciences and engineering - Laureano F. Escudero; Eva María Ortega; José Alonso (Stochastic Environmental Research and Risk Assessment, 2010)

Non-essential and essential trace element concentrations in meat from cattle reared under organic, intensive or conventional production systems - I. Blanco-Penedo; M. López-Alonso; M. Miranda; J. Hernández; F. Prieto; R.F. Shore (Food Additives & Contaminants: Part A, 2010)

Life‐history characteristics of the large Amazonian migratory catfish Brachyplatystoma rousseauxii in the Iquitos region, Peru - A. García Vásquez; J.‐C. Alonso; F. Carvajal; J. Moreau; J. Nuñez; J.‐F. Renno; S. Tello; V. Montreuil; F. Duponchelle (Journal of Fish Biology, 2009)
The main life‐history traits of the dorado Brachyplatystoma rousseauxii , a large Amazonian catfish undertaking the largest migration known for a freshwater fish species (from the nursery area in the estuary of the Amazon to the breeding zones in the head waters of the western Amazon basin close to the Andes), were determined from a 5 year sampling of >15 000 specimens in the Peruvian Amazon. The breeding season occurred during the falling and low‐water periods, which is hypothesized to be an adaptation to maximize the chances of young stages to reach the estuary. The size at first sexual maturity was slightly larger for females than males, c. 91 and 83 cm standard length ( L S ), respectively. Both males and females reproduce for the first time at >3 years old. The fecundity per spawning event ranged from 481 734 to 1 045 284 oocytes for females weighing 25 and 34 kg, respectively. Seasonal variations of body condition were similar among sexes, but differed between immature specimens that had a higher condition during the low‐water period and lower condition during rising waters, and mature individuals that showed the opposite pattern. The growth characteristics were estimated by L S frequency analysis. For females, the best fitting models gave a mean birth date in August, during the height of the breeding cycle, with the following von Bertalanffy growth function parameters: L S∞ = 153·3, K = 0·29 and t 0 =– 0·37 years. For males, the best fitting model gave a mean birth date in July, also during the height of the breeding period, with L S∞ = 142, K = 0·30 and t 0 =– 0·36 years. At a given age, females were systematically larger than males and the size difference increased with age. The largest females sampled (148 cm L S ) was 11 years old and the largest male (134 cm L S ) was 9 years old. The mortality estimates were higher for males total ( Z ) = 1·34, natural ( M ) = 0·52 and fishing ( F ) = 0·82 than for females ( Z = 0·98, M = 0·50, F = 0·48). The life‐history patterns of B. rousseauxii are discussed in light of the available knowledge about this species and the understanding of its complex life cycle.

U–Pb dating of granodiorite and granite units of the Los Pedroches batholith. Implications for geodynamic models of the southern Central Iberian Zone (Iberian Massif) - M. Carracedo; J. L. Paquette; A. Alonso Olazabal; J. F. Santos Zalduegui; S. García de Madinabeitia; M. Tiepolo; J. I. Gil Ibarguchi (International Journal of Earth Sciences, 2009)

Impact of point spread function of MSG-SEVIRI on active fire detection - A. Calle; J. -L. Casanova; F. González-Alonso (International Journal of Remote Sensing, 2009)

Coinfection is an important factor in epidemiological studies: the first serosurvey of the aoudad (Ammotragus lervia) - M. G. Candela; E. Serrano; C. Martinez-Carrasco; P. Martín-Atance; M. J. Cubero; F. Alonso; L. Leon (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Organochlorine Pesticide and Polychlorinated Biphenyl in Calves from North-West Spain - I. Blanco-Penedo; M. López-Alonso; M. Miranda; J. L. Benedito; R. F. Shore (Bulletin of Environmental Contamination and Toxicology, 2008)

Optimization tools and simulation methods for designing and evaluating a mining operation - F. G. Bastante; J. Taboada; L. Alejano; E. Alonso (Stochastic Environmental Research and Risk Assessment, 2008)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Growth patterns of a proximal terrigenous margin offshore the Guadalfeo River, northern Alboran Sea (SW Mediterranean Sea): glacio-eustatic control and disturbing tectonic factors - F. J. Lobo; A. Maldonado; F. J. Hernández-Molina; L. M. Fernández-Salas; G. Ercilla; B. Alonso (Marine Geophysical Research, 2008)

Validation of active forest fires detected by MSG‐SEVIRI by means of MODIS hot spots and AWiFS images - A. Calle; F. González‐Alonso; S. Merino de Miguel (International Journal of Remote Sensing, 2008)

Impacts of Roads, Hunting, and Habitat Alteration on Nocturnal Mammals in African Rainforests - WILLIAM F. LAURANCE; BARBARA M. CROES; NICAISE GUISSOUEGOU; RALPH BUIJ; MARC DETHIER; ALFONSO ALONSO (Conservation Biology, 2008)
Nocturnal mammals are poorly studied in Central Africa, a region experiencing dramatic increases in logging, roads, and hunting activity. In the rainforests of southern Gabon, we used spotlighting surveys to estimate abundances of nocturnal mammal species and guilds at varying distances from forest roads and between hunted and unhunted treatments (comparing a 130‐km 2 oil concession that was nearly free of hunting, with nearby areas outside the concession that had moderate hunting pressure). At each of 12 study sites that were evenly divided between hunted and unhunted areas, we established standardized 1‐km transects along road verges and at 50, 300, and 600 m from the road. We then repeatedly surveyed mammals at each site during 2006. Hunting had few apparent effects on this assemblage. Nevertheless, the species richness and often the abundance of nocturnal primates, smaller ungulates, and carnivores were significantly depressed within approximately 30 m of roads. Scansorial rodents increased in abundance in hunted forests, possibly in response to habitat changes caused by logging or nearby swidden farming. In multiple‐regression models many species and guilds were significantly influenced by forest‐canopy and understory cover, both of which are altered by logging and by certain abiotic variables. In general, nocturnal species, many of which are arboreal or relatively small in size (

Online Monitoring of Aluminium in Drinking Water with Fluorimetric Detection - A. Alonso-Mateos; M. J. Almendral-Parra; Y. Curto-Serrano; F. J. Rodríguez-Martín (Journal of Fluorescence, 2008)

Ozonized sunflower oil reduces oxidative damage induced by indomethacin in rat gastric mucosa - Z. Zamora; R. González; D. Guanche; N. Merino; S. Menéndez; F. Hernández; Y. Alonso; S. Schulz (Inflammation Research, 2008)

Insect Resistance Monitoring for Bt Maize Cultivation in the EU: Proposal from the Industry IRM Working Group - E. Alacalde; F. Amijee; G. Blache; C. Bremer; S. Fernandez; M. Garcia-Alonso; K. Holt; G. Legris; C. Novillo; P. Schlotter; N. Storer; B. Tinland (Journal of Consumer Protection and Food Safety, 2007)

MERIS‐FR potential for land use–land cover mapping in Spain - S. García‐Gigorro; F. González‐Alonso; S. Merino‐de‐Miguel; A. Roldán‐Zamarrón; J. M. Cuevas (International Journal of Remote Sensing, 2007)

MERIS Full Resolution data for mapping level‐of‐damage caused by forest fires: the Valencia de Alcántara event in August 2003 - F. González‐Alonso; S. Merino‐De‐Miguel; A. Roldán‐Zamarrón; S. García‐Gigorro; J. M. Cuevas (International Journal of Remote Sensing, 2007)

The marine sphingolipid-derived compound ES 285 triggers an atypical cell death pathway - M. Salcedo; C. Cuevas; J. L. Alonso; G. Otero; G. Faircloth; J. M. Fernandez-Sousa; J. Avila; F. Wandosell (Apoptosis, 2007)

Impacts of Roads and Hunting on Central African Rainforest Mammals - WILLIAM F. LAURANCE; BARBARA M. CROES; LANDRY TCHIGNOUMBA; SALLY A. LAHM; ALFONSO ALONSO; MICHELLE E. LEE; PATRICK CAMPBELL; CLAUDE ONDZEANO (Conservation Biology, 2006)
Road expansion and associated increases in hunting pressure are a rapidly growing threat to African tropical wildlife. In the rainforests of southern Gabon, we compared abundances of larger (>1 kg) mammal species at varying distances from forest roads and between hunted and unhunted treatments (comparing a 130‐km 2 oil concession that was almost entirely protected from hunting with nearby areas outside the concession that had moderate hunting pressure). At each of 12 study sites that were evenly divided between hunted and unhunted areas, we established standardized 1‐km transects at five distances (50, 300, 600, 900, and 1200 m) from an unpaved road, and then repeatedly surveyed mammals during the 2004 dry and wet seasons. Hunting had the greatest impact on duikers ( Cephalophus spp. ), forest buffalo ( Syncerus caffer nanus ), and red river hogs ( Potamochoerus porcus ), which declined in abundance outside the oil concession, and lesser effects on lowland gorillas ( Gorilla gorilla gorilla ) and carnivores. Roads depressed abundances of duikers, sitatungas ( Tragelaphus spekei gratus ), and forest elephants ( Loxondonta africana cyclotis ), with avoidance of roads being stronger outside than inside the concession. Five monkey species showed little response to roads or hunting, whereas some rodents and pangolins increased in abundance outside the concession, possibly in response to greater forest disturbance. Our findings suggest that even moderate hunting pressure can markedly alter the structure of mammal communities in central Africa. Roads had the greatest impacts on large and small ungulates, with the magnitude of road avoidance increasing with local hunting pressure.

Relationship between hepatitis C virus (HCV) and insulin resistance, endothelial perturbation, and platelet activation in HIV–HCV–coinfected patients under highly active antiretroviral treatment - G. F. Larrañaga; S. D. A. Perés Wingeyer; L. M. Puga; B. S. Alonso; J. A. Benetucci (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

HLA class I and class II frequencies in patients with cutaneous malignant melanoma from southeastern Spain: the role of HLA-C in disease prognosis - José A. Campillo; Jorge A. Martínez-Escribano; Manuel Muro; Rosa Moya-Quiles; Luis A. Marín; Olga Montes-Ares; Natalia Guerra; Paloma Sánchez-Pedreño; José F. Frías; José A. Lozano; Ana M. García-Alonso; M. Rocío Álvarez-López (Immunogenetics, 2006)

Favorable outcome of pneumonia due to Panton–Valentine leukocidin-producing Staphylococcus aureus associated with hematogenous origin and absence of flu-like illness - C. Alonso-Tarrés; M. L. Villegas; F. J. Gispert; M. C. Cortés-Lletget; A. Rovira Plarromaní; J. Etienne (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Zolpidem and triazolam do not affect the nocturnal sleep-induced memory improvement - Jaime Meléndez; Irina Galli; Katica Boric; Alonso Ortega; Leonardo Zuñiga; Carlos F. Henríquez-Roldán; Ana M. Cárdenas (Psychopharmacology, 2005)

Nitric oxide prevents the bacterial translocation and inhibits the systemic inflammatory response produced by implantation of a vascular prosthesis followed by Zymosan A - F. S. Lozano; M. B. Barros; M. J. Fresnadillo; F. J. García-Criado; A. Gomez-Alonso (Inflammation Research, 2005)

Effect of carticaine on the sarcoplasmic reticulum Ca2+-adenosine triphosphatase. II. Cations dependence - Delia Takara; Gabriel A. Sánchez; Augusto F. Toma; Patricia Bonazzola; Guillermo L. Alonso (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Pneumococcal bacteremia in children: an 8-year review in two hospitals in Barcelona - A. Prez; P. Sala; M. Gimnez; M. Sierra; A. Esteve; A. Alonso; M. Quesada; F. Raspall; V. Ausina; C. Rodrigo (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

GPS Monitoring in the N-W Part of the Volcanic Island of Tenerife, Canaries, Spain: Strategy and Results - J. Fernández; F. J. González-Matesanz; J. F. Prieto; G. Rodríguez-Velasco; A. Staller; A. Alonso-Medina; M. Charco (Pure and Applied Geophysics, 2004)

Nestin, a neuroectodermal stem cell marker molecule, is expressed in Leydig cells of the human testis and in some specific cell types from human testicular tumours - Maria V. T. Lobo; Maria I. Arenas; F. Javier M. Alonso; Gonzalo Gomez; Eulalia Bazn; Carlos L. Pano; Eldiberto Fernndez; Benito Fraile; Ricardo Paniagua; Alfredo Moyano; Enrique Caso (Cell and Tissue Research, 2004)

Discriminatory power of different arthropod data sets for the biological monitoring of anthropogenic disturbance in tropical forests - Yves Basset; Jacques F. Mavoungou; Jean Bruno Mikissa; Olivier Missa; Scott E. Miller; Roger L. Kitching; Alfonso Alonso (Biodiversity and Conservation, 2004)

Expression of porcine CD163 on monocytes/macrophages correlates with permissiveness to African swine fever infection - C. Snchez-Torres; P. Gmez-Puertas; M. Gmez-del-Moral; F. Alonso; J.M. Escribano; A. Ezquerra; J. Domnguez (Archives of Virology, 2003)

Lovastatin alters cytoskeleton organization and inhibits experimental metastasis of mammary carcinoma cells - Hernán G. Farina; Débora R. Bublik; Daniel F. Alonso; Daniel E. Gomez (Clinical & Experimental Metastasis, 2002)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Predator associated morphology in Galaxias platei in Patagonian lakes - D. Milano; V. E. Cussac; P. J. Macchi; D.E. Ruzzante; M. F. Alonso; P. H. Vigliano; M. A. Denegri (Journal of Fish Biology, 2002)
Among 158 Galaxias platei individuals, collected from nine deep Andean lakes and from one shallow lake on the Patagonian steppe, morphological characters associated with caudal fin length were negatively correlated with predation intensity as measured by the incidence of piscivory. Fish from lakes with high rates of piscivory had relatively short caudal fins and those from lakes with low piscivory had long caudal fins. It is hypothesized that in this species caudal fin length affects swimming ability and thus, ability to escape from predators. The population of G. platei from Lake Espejo with an intermediate level of piscivory contained individuals with both long and short caudal fins. Morphological variation within this lake was related to the exploitation of food resources and habitat; individuals with shorter tails ate more amphipods and inhabited shallower habitats. The results indicated that while the among‐lakes morphological variation in G. platei was influenced largely by differences in predation intensity, within‐lake morphological variation, where predation was intermediate, appeared to be affected by both predation and differences in the exploitation of food resources.

Natural antibodies to nematode biotinyl-enzymes in human sera - S. Lorenzo; R. Iglesias; E. Paniagua; I. Ansotegui; J. Alonso; F. Ubeira (Medical Microbiology and Immunology, 2001)

C and Sr isotopic evolution of carbonate sequences in NW Argentina: Implications for a probable Precambrian-Cambrian transition - A. N. Sial; V. P. Ferreira; A. J. Toselli; F. G. Aceñolaza; M. M. Pimentel; M. A. Parada; R. N. Alonso (Carbonates and Evaporites, 2001)

Antigenic and immunogenic properties of a chimera of two immunodominant African swine fever virus proteins - M. G. Barderas; F. Rodríguez; P. Gómez-Puertas; M. Avilés; F. Beitia; C. Alonso; J. M. Escribano (Archives of Virology, 2001)

Brain activity and fatigue during prolonged exercise in the heat - B. Nielsen; T. Hyldig; F. Bidstrup; J. González-Alonso; G.R.J. Christoffersen (Pflügers Archiv - European Journal of Physiology, 2001)

Characterisation of the RNA-dependent RNA polymerase from Rabbit hemorrhagic disease virus produced in Escherichia coli - A. López Vázquez; J. M. Martín Alonso; F. Parra (Archives of Virology, 2001)

A study on sampling design for optimal prediction of space–time stochastic processes - J. M. Angulo; M. C. Bueso; F. J. Alonso (Stochastic Environmental Research and Risk Assessment, 2000)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

G disulphide bond native conformation is required to elicit trout neutralizing antibodies against VHSV - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; J. M. Coll (Journal of Fish Diseases, 1999)

Effects of general anaesthetic procedures on mitochondrial function of human skeletal muscle - Ò. Miró; A. Barrientos; J. R. Alonso; J. Casademont; D. Jarreta; Á. Urbano-Márquez; F. Cardellach (European Journal of Clinical Pharmacology, 1999)

Effect of feeding extruded kidney bean diets on in vivo intestinal absorption of D-glucose - R. Alonso; S. Santidrián; F. Marzo (Journal of Physiology and Biochemistry, 1998)

Semi-parametric statistical approaches for space-time process prediction - J.M Angulo; W. González-Manteiga; M. Febrero-Bande; F. J. Alonso (Environmental and Ecological Statistics, 1998)

Body shape variation of three species of Percichthys in relation to their coexistence in the Limay River basin, in northern Patagonia - Víctor E. Cussac; Daniel Ruzzante; Sandra Walde; Patricio J. Macchi; Valeria Ojeda; Marcelo F. Alonso; María A. Denegri (Environmental Biology of Fishes, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Electron Microscopic In Situ Hybridization of Digoxigenin-dUTP-labelled DNA Probes with Drosophila Melanogaster Polytene Chromosomes - V. F. Semeshin; R. Artero; M. Perez-alonso; V. V. Shloma (Chromosome Research, 1998)

Use and abuse of placebo in phase III trials - F. Garca-Alonso; O. M. Bakke; X. Carn Cladellas; E. Guallar (European Journal of Clinical Pharmacology, 1998)

A state-space model approach to optimum spatial sampling design based on entropy - M. C. Bueso; J. M. Angulo; F. J. Alonso (Environmental and Ecological Statistics, 1998)

Programmed cell death in the pathogenesis of rabbit hemorrhagic disease - C. Alonso; J. M. Oviedo; J. M. Martín-Alonso; E. Díaz; J. A. Boga; F. Parra (Archives of Virology, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Inhibition of IL-2R and SLA class II expression on stimulated lymphocytes by a suppressor activity found in homogenates of African swine fever virus infected cultures - A. Canals; J. Domnguez; J. Tomillo; M. Babn; F. Alonso (Archives of Virology, 1995)

Sequence of the coding regions from the 3.0 kb and 3.9 kb mRNA - P. Britton; C. Lopez Otin; J. M. Martin Alonso; F. Parra (Archives of Virology, 1989)